2022
DOI: 10.1002/arch.21908
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Metarhizium anisopliae Ma6 and defense responses of host Phyllotreta striolata adults

Abstract: Entomopathogenic fungus as biological control agent plays a crucial role in the integrated management of insect pests.Metarhizium anisopliae Ma6 has been identified as a highly pathogenic strain against Phyllotreta striolata (Fabricius) (Coleoptera: Chrysomelidae), one of the most economically important and dominant insect pests damaging Brassica plants. The infection of M. anisopliae Ma6 on P. striolata was observed under stereomicroscopy and scanning electron microscopy (SEM), and biochemical defense respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…By 9 dpi, the activities of all three protective enzymes increased to varying degrees. In contrast, previous studies have shown that the activities of SOD, CAT, and POD increase and then decrease following infection with entomopathogens (Li et al, 2022; Xie et al, 2019). This may be because different species respond differently to infection with pathogens.…”
Section: Discussionmentioning
confidence: 69%
“…By 9 dpi, the activities of all three protective enzymes increased to varying degrees. In contrast, previous studies have shown that the activities of SOD, CAT, and POD increase and then decrease following infection with entomopathogens (Li et al, 2022; Xie et al, 2019). This may be because different species respond differently to infection with pathogens.…”
Section: Discussionmentioning
confidence: 69%
“…SOD is a metal protein which can neutralize active superoxide (ROS) in the cell, which is one of the key enzymes in the cell defense system to fight against superoxide damage [ 31 , 32 ]. In Beauveria bassiana (Bals.)…”
Section: Discussionmentioning
confidence: 99%
“…Vuill., SOD and CAT genes play an essential role in the host infection process of the fungus. In addition, they are vital for the antioxidant and ultraviolet tolerance of cells [ 32 , 33 ]. Studies have shown that SOD and CAT genes have important effects on the growth and development, tolerance, and virulence of fungi [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we reported the efficiency of seed and stem–leaf treatment strategies employing an EF BCA, M. anisopliae , to manage CFB and improve CFC production. The efficiencies of BCAs, such as M. anisopliae, have been studied for a long time on the laboratory scale, identifying several strains causing >50% mortality in the CFB [ 6 ]; however, only a few commercial products based on these strains as a soil treatment or stem–leaf spraying treatment are used in fields.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of entomopathogenic nematodes, fungi, bacteria, and parasitoids as BCAs has been rigorously investigated at the laboratory scale. Recent research reported that M. anisopliae strain Ma6 is highly pathogenic against CFB with a 7-day cumulative mortality rate of 91.11% and a median lethal time (LT 50 ) of 4.09 days [ 6 ]. While both nematode species Steinernema carpocapsae and Heterorhabditis indica were capable of reducing populations of the soil-dwelling stages of CFB [ 7 ].…”
Section: Introductionmentioning
confidence: 99%